Comparative analysis of biodiversity, physiology, and anatomical adaptations in riparian flora exposed to industrial pollution stress - Mansour K. Gatasheh; Toqeer Abbas; Shifa shaffique; Sang-Mo Kang; In-Jung Lee; Anis Ali shah (Scientific Reports)
Abstract Anthropogenic activities such as industrial pollution of water bodies possess threat to floras leading to extinction and endangerment. This study investigates the impact of industrial pollution on vegetation along River Chenab and its associated drains. Rivers and channels transporting industrial effluents have been determined to be significantly contaminated. The contamination was evidenced by the acidic and alkaline nature of industrial effluents, salinity, total dissolved solids, and the sodium absorption ratio. The research revealed that the pollution in the region severely impacts the native vegetation, resulting in a marked decline in density, frequency, relative density, and relative frequency across 10 sites, including three drain sites and one non-polluted site. Four plant species, Calotropis procera, Eclipta alba, Phyla nodiflora, and Ranunculus sceleratus exhibited tolerance to pollution and were present at all sites during all seasons. Anatomical modifications, such as increased root aerenchyma and vascular bundles, enabled these plants to thrive in polluted environments. The study highlights the importance of these species in phytoremediation and their potential for use in restoring degraded ecosystems.